IPO pricing and allocation: a survey of the views of institutional investors - Jenkinson, T; Jones, H (Oxford University Press, 2009)
Despite the central importance of investors to all initial public offering (IPO) theories, relatively little is known about their role in practice. This article is based on a survey of how institutional investors assess IPOs, what information they provide to the investment banking syndicate, and the factors they believe influence allocations. We find that investor characteristics, in particular brokerage relationships with the bookrunner, are perceived to be the most important factors influencing allocations, which supports the view that IPO allocations are part of implicit quid pro quo deals with investment banks. The survey raises doubts as to the extent of information production or revelation.